Colorimetric determination of bromate in drinking water using methyl red immobilized into polymethacrylate matrix - Saranchina, Nadezhda V.; Trifonova, N. S.; Urazov, E. V.; Gavrilenko, Nataliya A.; Gavrilenko, Mikhail A. (International journal of environmental analytical chemistry)
This article presents solid-phase spectrophotometric method of bromate determination using methyl red immobilised into transparent polymethacrylate matrix. The method is based on oxygenation of the indicator immobilised into the matrix by a bromate. We discovered the optimal conditions for bromate determination, studied the effect of interference of the foreign ions, and evaluated the analytical performance of the suggested method. The method we developed makes it possible to quantify the content of a bromate in the concentration range of 0.1-1.0 mg·L−1 with the limit of detection 0.01 mg·L−1. The mean relative standard deviation of the results was ≤1.2%, which confirmed reproducibility of this assay technique. We demonstrated usability of the suggested method for detection of bromates in drinking water using solid-phase spectrophotometry without any preliminary sample preparation. Polymethacrylate matrix with methyl red immobilised into it can be used as a ready-made analytical form for the rapid visual bromate determination test.